Characteristics of Tularemia Agent Strains Isolated from Patients and Small Rodents during Tularemia Epidemic in Khanty-Mansiisk in 2013 - V. Pavlov M.; I. Kozlova I.; A. Mokrievich N.; O. Shutko D.; V. Timofeev S.; R. Mironova I.; T. Kuznetsova S.; N. Faizullina M.; T. Kudryavtseva Yu.; T. Kombarova I.; I. Dyatlov A.; В. Павлов М.; et al. (Problems of Particularly Dangerous Infections, 2015)
The paper contains the data on isolation of Francisella tularensis cultures from humans and rodents during tularemia epidemic in Khanty-Mansiisk in August-September, 2013. All the obtained F. tularensis strains (six cultures of tularemia microbe from patients, and four cultures - from small rodents caught in the territory of the city and its suburbs) fall under Holarctic subspecies, are highly virulent for the laboratory mice, resistant to erythromycin, ampicillin, and cephalosporin, but sensitive to amikacin, tetracycline, doxycycline, and gentamycin. Using 25-locus-MLVA typing it is demonstrated that the strains under study form a common cluster on the phylogenetic tree along with F. tularensis strains previously isolated in the territory of the Southern Urals and Kazakhstan. All the strains from the foci are closely related ones, and based on the investigations of hyper-variable Ft-M3 locus, fall into four groups. The strains, isolated from humans, combine into three groups, and the strains isolated from rodents - into two, and notably that one of the groups of Khanty-Mansiisk cluster comprises the strains isolated from both humans and rodents. В работе приведены данные о выделении культур Francisella tularensis от людей и грызунов во время эпидемии туляремии среди жителей Ханты-Мансийска в августе-сентябре 2013 г. Все выделенные штаммы F. tularensis (шесть культур туляремийного микроба от больных и четыре - от мелких грызунов, отловленных в городе и его окрестностях) относятся к голарктическому подвиду, высоковирулентны для лабораторных мышей, устойчивы к эритромицину, ампициллину и цефалоспоринам, но чувствительны к амикацину, тетрациклину, доксициклину и гентамицину. Методом MLVA по 25 локусам показано, что исследованные штаммы располагаются одним кластером на филогенетическом дереве вместе со штаммами F. tularensis , выделенными ранее на территории Южного Урала и Казахстана. Все штаммы из очага являются близкородственными и, по данным анализа гипервариабельного локуса Ft-M3, подразделяются на четыре группы. Штаммы, выделенные от людей, образуют три группы, а штаммы, выделенные от мелких грызунов - две, причем в одну из групп Ханты-Мансийского кластера попали штаммы, выделенные как от людей, так и грызунов.